Effects of Steam Sterilization and Recycling on the Mechanical and Surface Properties of 3D-Printed Biodegradable PLA and Re-PLA Materials - Karayer, Yunus; Altinsoy, Sakir; Koc, Gokce; Can, Diyadin; Togar, Yunus Emre (MDPI, 2025)
Polylactic acid (PLA) is an eco-friendly polymer known for its biodegradability and biocompatibility, yet its properties are sensitive to recycling and sterilization. These processes may cause chain scission and structural irregularities, leading to reduced strength, brittleness, or unpredictable deformation. In this study, PLA and recycled PLA (Re-PLA) specimens were produced by FDM 3D printing with different infill rates (25%, 50%, 75%), layer thicknesses (0.15, 0.20, 0.25 mm), and printing orientations (0 degrees, 45 degrees, 90 degrees). Steam sterilization at 121 degrees C and 1 bar for 15 min simulated biomedical conditions. Mechanical, surface, degradation, and biocompatibility properties were examined using three-point bending, roughness measurements, SEM, and cell viability tests. Results showed that infill rate was the main parameter affecting flexural strength and surface quality, while orientation increased roughness. Sterilization and recycling made deformation less predictable, particularly in St-Re-PLA. SEM revealed stronger bonding at higher infill, but more brittle fractures in PLA and Re-PLA, while sterilized specimens showed ductile features. No visible degradation occurred at any infill level. Regression analysis confirmed that second-order polynomial models effectively predicted flexural strength, with layer thickness being most influential. These findings provide critical insights into optimizing PLA and Re-PLA processing for biomedical applications, particularly in the production of sterilizable and recyclable implantable devices.
Keywords: PLA; 3D printer; sterilization; recycling; mechanical properties; biocompatibility; PROCESS PARAMETERS; TENSILE; OPTIMIZATION; STRENGTH; IMPACT; Polymer Science